Dem quality assessment with a 3d printed gravel bed applied to stereo photogrammetry. (June 2014) - Bertin, S.; Friedrich, H.; Delmas, P.; Chan, E.; Gimel'farb, G.
Abstract Using stereo photogrammetry to obtain digital elevation models (DEMs) for surface topography analysis is becoming popular in hydraulic research, especially for coarse gravel beds. This paper assesses the DEM quality by using a realistic 3D printed gravel‐bed model, with known elevations every 0·25 mm, as ground truth. Two Nikon D5100 cameras and non‐proprietary photogrammetric software for camera calibration and DEM reconstruction are used for the study. A measured DEM is compared point by point with the ground truth and displays a very high measurement accuracy. The 3D printing of ground truths facilitates fast and versatile evaluation of both the DEM quality and the sensitivity of its errors to changes in surface topography and collection parameters. It has the potential to streamline evaluations of calibration and image quality, as well as error filtering strategies. Ultimately, 3D printed models will help in exploring stereomatching error reductions in occluded regions and defining the most suitable strategy for gravel‐bed DEM collection, both in air and through water.